2020
DOI: 10.1021/acs.jpclett.0c01322
|View full text |Cite
|
Sign up to set email alerts
|

Multiquantum Chemical Exchange Saturation Transfer NMR to Quantify Symmetrical Exchange: Application to Rotational Dynamics of the Guanidinium Group in Arginine Side Chains

Abstract: Chemical exchange saturation transfer (CEST) NMR experiments have emerged as a powerful tool for characterizing dynamics in proteins. We show here that the CEST approach can be extended to systems with symmetrical exchange, where the NMR signals of all exchanging species are severely broadened. To achieve this, multiquantum CEST (MQ-CEST) is introduced, where the CEST pulse is applied to a longitudinal multispin order density element and the CEST profiles are encoded onto nonbroadened nuclei. The MQ-CEST appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 35 publications
(84 reference statements)
1
13
0
Order By: Relevance
“…A recent 13 C-detected multiquantum chemical exchange saturation transfer (MQ-CEST) method allows access to Nη chemical shifts through the Cζ-Nε correlation maps that are not affected by the rotational exchange and enables characterization of the rotational dynamics of guanidinium groups in arginine side chains. 35 The involvement of an arginine side chain in a salt bridge can potentially lead to a change in the chemical shift difference between the two Nη nuclei (Δω in rad/s −1 ) or reduce the rotational dynamics of guanidinium groups (k ex in s −1 ). To investigate the potential effect of salt bridge formation on the rotational dynamics of the guanidinium group in Arg5 of Aβ40, we measured the MQ-CEST of Aβ40 and compared it with that of the free arginine as a reference (Figure 4c).…”
mentioning
confidence: 99%
“…A recent 13 C-detected multiquantum chemical exchange saturation transfer (MQ-CEST) method allows access to Nη chemical shifts through the Cζ-Nε correlation maps that are not affected by the rotational exchange and enables characterization of the rotational dynamics of guanidinium groups in arginine side chains. 35 The involvement of an arginine side chain in a salt bridge can potentially lead to a change in the chemical shift difference between the two Nη nuclei (Δω in rad/s −1 ) or reduce the rotational dynamics of guanidinium groups (k ex in s −1 ). To investigate the potential effect of salt bridge formation on the rotational dynamics of the guanidinium group in Arg5 of Aβ40, we measured the MQ-CEST of Aβ40 and compared it with that of the free arginine as a reference (Figure 4c).…”
mentioning
confidence: 99%
“…In both CEST and R 1q RD experiments, an accurate measurement of the radiofrequency (RF) field strength is essential for quantifying thermodynamic, kinetic and structural parameters of the conformational exchange event [11,36,37]. Over the years, a number of methods have been developed for determining the amplitude of the B 1 field, beginning with the sideband strategy outlined by Bloch [38] and demonstrated by Anderson in 1956 [39].…”
Section: Introductionmentioning
confidence: 99%
“…The slow relaxation of the 13 C nuclei in these deuterated systems means that spectra can be recorded on even relatively large proteins, providing a uniquely detailed insight into the structure and dynamics of protein side chains. It has also been shown that even on protonated samples the additional steps in a pulse sequence required to return the magnetisation back to protons and subsequent signal loss due to solvent exchange can result in { 1 H-excite, 13 C-detect} sequences having higher overall sensitivity in certain cases [13,14] . Despite these clear advantages, an important issue that affects 13 C direct detection experiments of uniformly labelled samples is the presence of large one bond 13 C- 13 C scalar couplings, typically 30-55 Hz in size, which evolve during acquisition [15] .…”
Section: Introductionmentioning
confidence: 99%